Promoting salutogenic pathways to health through complementary and integrative health approaches - Quinlan, Erin Burke; Baumgartner, Jennifer; Chen, Wen G.; Weber, Wendy; Horgusluoglu, Emrin; Edwards, Emmeline (Frontiers in Psychology, 2024)
Health restoration and disease prevention are important strategies to achieve health and well-being. This Perspective provides a conceptual overview of the key concepts of salutogenesis (health restoration), chronic stress, resilience, and emotional well-being, and describes how they are distinct and interrelated. We posit, and demonstrate through scientific evidence, that complementary and integrative health approaches, including mind and body interventions, can be used to mitigate the effects of chronic stress and promote salutogenic pathways. Our goal is to identify research gaps and opportunities and suggest ways to advance the knowledge base for mechanistic and clinical research in this field.